SYSTEMATIC LITERATURE REVIEW TENTANG DETERMINAN KEPATUHAN WAJIB PAJAK PELAKU UMKM DI INDONESIA - Fania Agustina; Sukemi Kamto Sudibyo; Zahra Dinul Khaq (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Taxes are a primary source of state revenue and play a vital role in supporting national development. However, Indonesia still faces serious challenges in achieving its annual tax revenue targets. One of the main factors contributing to this low revenue is the low level of tax compliance, particularly among the Micro, Small, and Medium Enterprises (MSMEs). MSMEs contribute 61.07% to Gross Domestic Product and employ 97% of the national workforce, yet their tax potential remains underutilized. This literature review analyzes the determinants of MSME taxpayer compliance through a review of various empirical studies. Factors such as tax knowledge, tax socialization, the quality of tax authorities' services, and tax incentives and sanctions were found to play significant roles in shaping taxpayer compliance behavior. Furthermore, tax awareness is also a significant moderating variable in the relationship between socialization and compliance. This study demonstrates the importance of an integrated approach between education, services, and law enforcement in improving MSME tax compliance. These findings provide a conceptual basis for formulating more effective and equitable fiscal policy strategies.